2018
DOI: 10.2355/isijinternational.isijint-2017-512
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Embrittlement and Local Characterization at Crack Initiation Associated with Phase Transformation of High-strength Steel Containing Retained Austenite

Abstract: States of hydrogen present in high-strength steels for use as bearing steel SUJ2 and hydrogen embrittlement susceptibility were examined using thermal desorption analysis (TDA) and tensile tests. SUJ2 specimens containing the retained austenite phase (γ R ) in the martensitic phase exhibited three hydrogen desorption peaks in the TDA profile. Two of the peaks desorbed at higher temperatures decreased with a decreasing amount of γ R , indicating they corresponded to desorption associated with γ R . Fracture str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…pct retained austenite, hydrogen desorption behavior in a TDA measurement was affected by retained austenite present in a film shape with a maximum length of about 3 lm on the prior austenite grain boundary. [18] These previous reports on high-carbon martensitic steel with retained austenite suggest that film and/or plate-like retained austenite ranging from sub-lm to hundreds of lm in size has hydrogen trapping capability. In the present study, HC-M presumably contained similar retained austenite in terms of morphology, size, and remaining area within the martensitic microstructure.…”
Section: Hydrogen Trapping Sites For High-carbon Martensitic Steelmentioning
confidence: 92%
See 2 more Smart Citations
“…pct retained austenite, hydrogen desorption behavior in a TDA measurement was affected by retained austenite present in a film shape with a maximum length of about 3 lm on the prior austenite grain boundary. [18] These previous reports on high-carbon martensitic steel with retained austenite suggest that film and/or plate-like retained austenite ranging from sub-lm to hundreds of lm in size has hydrogen trapping capability. In the present study, HC-M presumably contained similar retained austenite in terms of morphology, size, and remaining area within the martensitic microstructure.…”
Section: Hydrogen Trapping Sites For High-carbon Martensitic Steelmentioning
confidence: 92%
“…As some researchers have reported, retained austenite and/or interfaces between retained austenite and the matrix can serve as hydrogen trapping sites in C-Mn-Fe alloys. [16,18,46] Tsubakino et al reported that the effective hydrogen diffusion coefficient (D H ) of two types of steels, namely, tempered martensite steel and steel with retained austenite of 26.3 vol. pct, having the same tensile strength of 1200 MPa and shaped as a plate from 20 to 100 lm in thickness, were D H % 1.5 9 10 À10 m 2 /s and D H % 1.3 9 10 À11 m 2 /s, respectively.…”
Section: Hydrogen Trapping Sites For High-carbon Martensitic Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypereutectoid steels possess high hardness without requiring complicated surface treatments such as carburization. For example, as a typical hypereutectoid steel, JIS-SUJ2 steel with high C and Cr contents (i.e., 0.95-1.10C and 1.30-1.60Cr), is practically used as a bearing steel with a martensitic microstructure as the matrix and globular carbide particles 1,2) . However, the metals demonstrate a trade-off relationship, i.e., hypereutectoid steels have high hardness but severe brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical hypereutectoid steel, JIS-SUJ2 steel with high C and Cr contents is widely known as a bearing steel with a martensitic microstructure as the matrix and globular carbide particles. 3,4) However, as is generally known in the field of metallic materials, there is a trade-off between strength and ductility, meaning that as strength increases, ductility tends to decrease. Accordingly, hypereutectoid steels are characterized by high hardness and brittleness.…”
Section: Introductionmentioning
confidence: 99%